2013
DOI: 10.2298/abs1302611g
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water stress and salinity on growth and physiology of tomato (Lycopersicon esculentum Mil.)

Abstract: Carotenoids like lycopene are important pigments found in photosynthetic pigment-protein complexes in plants. They are responsible for the bright colors of fruits and vegetables and perform various functions in photosynthesis. Our research has shown that the application of moderate salt stress on tomato plants can enhance lycopene and potentially other antioxidant concentrations in fruits. The increase in lycopene in response to salt stress in the tomato fruits varied from 20% to 80%. Although the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 44 publications
6
44
2
1
Order By: Relevance
“…Water deficit is one of the major limiting factors for crop production, and several studies have been performed to verify its effect on tomato growth, yield, secondary metabolite production, and gene expression (Nuruddin et al, 2003;Sánchez-Rodríguez et al, 2011;Giannakoula and Ilias, 2013;Sacco et al, 2013). Previous work also studied the relationship between tomato and AM fungi under WS (Dell'Amico et al, 2002;Subramanian et al, 2006;Aroca et al, 2008;Wang et al, 2014;Ruiz-Lozano et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Water deficit is one of the major limiting factors for crop production, and several studies have been performed to verify its effect on tomato growth, yield, secondary metabolite production, and gene expression (Nuruddin et al, 2003;Sánchez-Rodríguez et al, 2011;Giannakoula and Ilias, 2013;Sacco et al, 2013). Previous work also studied the relationship between tomato and AM fungi under WS (Dell'Amico et al, 2002;Subramanian et al, 2006;Aroca et al, 2008;Wang et al, 2014;Ruiz-Lozano et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Proline is generally considered as a good indicator of environmental stress in tomato (Clausen, 2005) and there are many reports describing an increase in Pro contents as a response to water or salt stress in this species (Babu et al, 2012;Ghorbanli et al, 2013;Giannakoula and Ilias, 2013;Inal, 2002;Handa et al, 1986;Nahar and Gretzmacher, 2002;Umebese et al, 2009;Yokas et al, 2008), although it should be mentioned that data specific for cherry tomatoes are rather scarce (Maggio et al, 2007;Rosales et al, 2007). What is not so clear is the possible contribution of Pro accumulation to the (relative) resistance of tomato to salinity.…”
Section: Malondialdehydementioning
confidence: 99%
“…As for other osmolytes, besides their role in osmoregulation, both compounds can act as 'low-molecular-weight chaperons', contributing to maintain the active conformation of macromolecules in stressed plants, and participate in detoxification of ROS. Moreover, Pro and GB seem to be papers reporting the effects of both salinity and drought on the same plant material (Giannakoula and Ilias, 2013). These two adverse environmental conditions, which will worsen as a consequence of climate change, could seriously affect tomato production in Mediterranean countries in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental stresses such as salt [28][29][30][31] and cadmium [32][33][34][35] can also affect photosynthetic pigments and inhibit photosynthesis. It was shown that PSII efficiency depends on pigment concentration and structure [36].…”
mentioning
confidence: 99%